Antimicrobial activity of nutmeg (Myristica fragrans Houtt.) and sensory attribute of beef treated with the nutmeg extract - Zakaria, Maya Puteri Malina (2015)
Antimicrobial and antioxidant of nutmeg were studied intensively in research and showed potential as antimicrobial and antioxidant agent apart. There were no report on antioxidant and antibacterial potential of nutmeg extract on any beef product. Beef muscles undergo several changes that can affect their safety (foodborne pathogens growth) and sensory attributes such as colour and flavor during storage. Therefore, there is a need to find an alternative method to control and maintain the safety and quality of raw beef during storage. The objective of this study is to evaluate the antimicrobial activity of nutmeg and to determine the effect of nutmeg extract towards the microorganism growth and sensory attributes of treated beef (lipid oxidation, colour, pH, texture, nutrition value). In this study, application of nutmeg (Myristica fragrans Houtt.) extract at different concentrations; 0.25%, 0.65%, 1.25%, 2.50% and 5.00% (g/ml) were used to treat raw beef (2.5 2.5 1.0 cm; 4 ± 0.5 g). Samples were then individually packed in overwrapped trays and stored for 3 weeks at -18 ± 2oC and 4oC ± 2oC. The treated raw beef were evaluated at 0, 1, 4, 7, 10, 14 and 21 days of storage. The results showed Bacillus subutilis, Esherichia coli, Klebsiella pneumonia and Listeria monocytogene was susceptible to nutmeg extract. The antimicrobial activities of nutmeg extract were not significantly affected by pH (3, 7, and 11) and temperatures (121˚C). There were significant differences on reduced number of bacterial count of beef with the concentrations of extract. Treatment at 5.00% showed the strongest bactericidal efficacy among all concentrations on L. monocytogenes, E. coli, by reductions of 2.10 and 4.54 log10 CFU/g, respectively stored at -18 ± 2°C. Treated beef starting at concentration 1.25% and above resulted significantly different (p<0.05) on inhibition of microbial growth stored at 4 ± 2°C. This results show that nutmeg extract effectively has antimicrobial effect on beef, not because of the temperature effect. Lipid oxidation analysis was identified using TBARS method. There were significant difference (p<0.05) on TBARS value of beef with the concentrations of extract. Extract at concentration of 1.25% and above inhibited TBARS value able to maintain the lipid oxidation of beef at both temperature. 1.25% of extract was also able to maintain the redness (a*) of treated beef compared to untreated beef during both temperatures. Treated beef with nutmeg extract able to maintain the pH value of normal conditions throughout the storage for both temperatures. There was a significant difference (p<0.05) on hardness with untreated and treated samples starting at 7th day of storage. There was no significant difference in term of protein content in all treated or untreated samples. However, fat and moisture content were significantly different (p<0.05) by the concentration of nutmeg extract. Overall, 1.25% of nutmeg extract was chosen based on best combination of sensory evaluation scores together with all analysis result to maintain the safety and quality of beef as well as maintaining organoleptic properties. From this study indicated that nutmeg extract showed a potential preservation ingredient and increase shelf life of beef without changes in quality, nutritional and sensory characteristics.